2024
DOI: 10.1101/2024.05.15.594343
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adventitial fibroblasts direct smooth muscle cell-state transition in pulmonary vascular disease

Slaven Crnkovic,
Helene Thekkekara Puthenparampil,
Shirin Mulch
et al.

Abstract: Pulmonary vascular remodeling is a progressive pathological process characterized by functional alterations within pulmonary artery smooth muscle cells (PASMC) and adventitial fibroblasts (PAAF). Mechanisms driving the transition to a diseased phenotype remain elusive. Utilizing a combination of transcriptomic and proteomic profiling, along with phenotyping of source-matched cells from healthy controls and individuals with idiopathic pulmonary arterial hypertension (IPAH), our investigation uncovered that whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Ultimately, they concluded that the maintenance and cell-state transition of PASMCs is partly dependent on external cues provided by neighboring PAAFs using a source-matched PASMC and PAAF co-culture model. These results underscore the role of PAAFs as signaling hubs involved in orchestrating heterotypic-cell-state maintenance and transitions [ 102 ].…”
Section: Fibroblasts’ Contribution To Pulmonary Vascular Remodeling I...mentioning
confidence: 83%
See 1 more Smart Citation
“…Ultimately, they concluded that the maintenance and cell-state transition of PASMCs is partly dependent on external cues provided by neighboring PAAFs using a source-matched PASMC and PAAF co-culture model. These results underscore the role of PAAFs as signaling hubs involved in orchestrating heterotypic-cell-state maintenance and transitions [ 102 ].…”
Section: Fibroblasts’ Contribution To Pulmonary Vascular Remodeling I...mentioning
confidence: 83%
“…Crnkovic et al have reported that pulmonary vascular remodeling is associated with a skewed cellular communication on a single-cell level to define the pathological vascular remodeling process of PAH centered on PAAFs and SMCs [ 50 ]. Their most recent findings further uncovered cell-type-specific phenotypic shifts and identified PAAFs as a source of secreted factors that regulate the PASMC state [ 102 ]. In this study, Crnkovic and colleagues applied integrative omics and a network-based analysis combined with targeted phenotypic screens to identify common cell-type and cell-state distinct cellular behaviors and examined the bidirectional cell communication between source-matched human PASMCs and PAAFs from healthy controls and IPAH patients.…”
Section: Fibroblasts’ Contribution To Pulmonary Vascular Remodeling I...mentioning
confidence: 99%